1999
DOI: 10.1211/0022357991777001
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Arctigenin, a Lignan Compound, on Tumour Necrosis Factor-α and Nitric Oxide Production, and Lymphocyte Proliferation

Abstract: We have investigated the immunomodulatory effects of arctigenin, a dibenzyl butyrolactone lignan compound, on tumour necrosis factor (TNF)-alpha and nitric oxide (NO) production, and lymphocyte proliferation. Arctigenin inhibited strongly TNF-alpha production by lipopolysaccharide-stimulated murine macrophage RAW264.7 and differentiated human macrophage U937 with IC50 values of 5.0 and 3.9 microM, respectively, without displaying cytotoxicity. The TNF-alpha inhibitory effect of arctigenin in lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 26 publications
1
46
0
1
Order By: Relevance
“…Arctigenin has also been reported to modulate immunologic responses (25) and to induce apoptosis in colon cancer cell lines (22). Therefore, the mechanism of antitumor activity of this agent may not be simple and the results of the present study suggest the involvement of the Akt pathway.…”
Section: Discussionmentioning
confidence: 69%
“…Arctigenin has also been reported to modulate immunologic responses (25) and to induce apoptosis in colon cancer cell lines (22). Therefore, the mechanism of antitumor activity of this agent may not be simple and the results of the present study suggest the involvement of the Akt pathway.…”
Section: Discussionmentioning
confidence: 69%
“…Arctigenin is the main active ingredient in Fructus arctii (Cho et al, 1999). Takasaki et al (2000) showed antitumor effects of both arctiin and arctigenin in suppression of mouse skin cancer, which was obtained from the aerial part of Saussurea medusaas.…”
Section: Discussionmentioning
confidence: 99%
“…Par ailleurs, si l'on se réfère aux expérimen-tations tant in vitro que chez l'animal [4], ainsi qu'à des données épidémiologiques [5], ces actions résulte-raient de leurs propriétés phyto-oestrogènes. En effet, le sécoisolaricirésinol et le matairésinol sont métaboli-sés par les bactéries de la flore intestinale des mammifères en entérolignanes, respectivement l'entérodiol et l'entérolactone ( Figure 1B).…”
Section: Rôle Des Propriétés Phyto-oestrogènes Des Lignanesunclassified